Perlindungan Hukum terhadap Pencipta atas Pencatatan Suatu Ciptaan yang Sama - Riko Sulung Raharjo; M. Khoidin; Ermanto Fahamsyah (Lentera Hukum, 2018)
Copyright recognizes a declarative system in which the state automatically protects a creation after it was born, without having to be preceded by registration. Article 64 of Copyrights Act Number 28 of 2014 (Copyright Act) confirms the registration, even though it is not a necessity for the creator. This study aims to examine and analyze the legal consequences, forms of legal protection, as well as the future conception of regulations relating to the recording of similar work, by using legal research as its method. The results of the study indicate that the legal consequences on the similar work to the registration, inter alia, the abolition of the power of law for the registration of works, compensation for the creator, and criminal threats. Based on the theory of legal certainty, a provision is a form of legal certainty provided by the Copyright Law. There is a form of legal protection for the creator of the registration of the similar creation, inter alia, the abolition of the power of the law for registering the work by the court, the creator has the right to compensation, and the creator has the right to sue criminally. Based on the theory of legal protection, a provision is a form of protection provided by the Copyright Law. The future conception of the regulation of registration of creation, so that it can provide legal protection against the creator through the renewal related to the addition of authority and procedures in conducting checks for ministers in the case of the registration of creation since it was first realized and announced. Based on the theory of legal certainty and the benefits of law, change and renewal can provide legal certainty and legal benefits for the creator and his creation. Keywords: Creator, Recording of Creations, Same Creations